Epidemiological profile of snakebites in Rio de Janeiro, Brazil, 2001-2006 - Machado,C (2012)
All snakebites registered in Rio de Janeiro state, Brazil, between 2001 and 2006 were analyzed. Of these, the snake species involved was identified in 2,431 cases, most of which were caused by Bothrops (2,347). Most victims were male (78.4%) and the age group most frequently attacked was between 20 and 39 years (38.4%). As for severity, 1,118 (45.9%) were classified as minor, 748 (30.7%) as moderate, and 209 (8.6%) as severe. Progression towards complete cure occurred in 1,567 patients; 39 had sequelae; three died; and clinical outcomes were not monitored in 822 cases. The time between bite and first medical attention was less than three hours in 74.6% of cases. Most occurred in municipalities with vast areas of preserved Atlantic Forest: Angra dos Reis (208), Rio de Janeiro (197), Parati (186), Teresópolis (134), and Petrópolis (110). Accident frequency was highest between November and April, in which the daily average is practically twice that observed in other months. Although results show that Rio de Janeiro state has a good level of medical care, it could be improved by creating multidisciplinary teams that include doctors, biologists, and nurses. The Vital Network for Brazil helps to promote a stimulating environment for this type of training, with both traditional courses and distance learning. Training hours must be increased to improve the skills of professionals responsible for victim care.